Assessing the Potential Regrowth Ability of Microalgae Using Hull Cleaning Wastewater from International Commercial Ships - Young Kyun Lim; Moonkoo Kim; Kyoungsoon Shin; Taekhyun Kim; Chung Hyeon Lee; Ji Nam Yoon; Seung Ho Baek (Journal of Marine Science and Engineering, 2023)
Ship biofouling is recognized as a significant pathway for the introduction and spread of invasive organisms. The in-water cleaning of ship hulls generates wastewater that includes antifouling paint residues and biofouling organisms, which inevitably leak into the marine environments, resulting in substantial adverse effects on marine ecosystems. To assess the impact of hull cleaning wastewater (HCW) on microalgae, we conducted microcosm experiments using HCW including attached microalgae. The experiments consisted of a total of 12 combined trials, including the following groups: ambient seawater as a control, the 5% HCW group (HCW), and the 5% HCW + nutrient addition group (HCW+N), conducted at temperatures of 15 and 20 °C, respectively. The Chl. a concentrations in the water column in the control group exhibited maximum values on day 1 (5.24 μg L−1 at 15 °C and 12.37 μg L−1 at 20 °C), but those of the treatments were at low levels, below 2 μg L−1 at both temperatures. On the other hand, the Chl. a concentrations on plastic plates were higher in the treatments than in the control group. Specifically, the Fv/Fm ratio in the water column, which indicates photosynthetic activity, was significantly higher in the control group compared to both the HCW and HCW+N groups at 15 and 20 °C (p < 0.05). This suggests that the growth of water column phytoplankton was inhibited following HCW inoculation. However, there were no significant differences in the Fv/Fm on plastic plates between the control and HCW treatment groups, implying that the periphyton maintained a high photosynthetic capacity even in the presence of HCW treatments. The elution of particulate copper in HCW was observed, which was considered as the main reason for the growth of phytoplankton. Our study results suggest that the runoff of HCW in the marine environment has a greater negative effect on phytoplankton than on periphyton, which can lead to changes in microalgae community composition and a decrease in productivity in the marine environment. Therefore, it is crucial to manage HCW runoff based on scientific assessments to minimize the ecological risks associated with the removal of biofilm or slime from ship biofouling during in-water hull cleaning.